Axial pattern skin flaps in cats: 8 cases (2000-2015) - GAVRIILIDOU (Ο. ΓΑΒΡΙΗΛΙΔΟΥ) O.; PAPAZOGLOU (Λ.Γ. ΠΑΠΑΖΟΓΛΟΥ) L. G.; KOUKI (Μ. ΚΟΥΚΗ) M.; STRANTZIA (Ε. ΣΤΡΑΝΤΖΙΑ) E.; GIANNOULI (Μ. ΓΙΑΝΝΟΥΛΗ) M.; MENTZIKOF (Λ. ΜΕΝΤΖΙΚΩΦ) L.; PINOPOULOS (Σ. ΠΙΝΟΠΟΥΛΟΣ) S. (Journal of the Hellenic Veterinary Medical Society, 2018)
Eight female cats of various breeds and median age of 4.5 years, with cutaneous defects in the limbs and trunk which were managed with axial pattern flaps, are described. Skin defects were caused by trauma or tumor excision. The defects were located in the medial aspect of the thigh in 2 cats, the lateral aspect of the thigh in 2, the left axilla in 2, the sternal and inguinal area in 2 and the dorsolateral abdomen and lumbar region in 1 cat. Totally 9 flaps were used including caudal superficial epigastric flap (4), thoracodorsal flap alone (1) or combined with omentalization (1), elbow fold flap and flank fold flap (2). All flaps survived and small dehiscences were found in 2 cats. All cats were healthy after a median follow up time of 13 months. The use of axial pattern flaps is a very effective method for the coverage of large skin defects in cats.